Reconsideration of Research Methodologies: A Look at Major Trails and Concepts - Cibangu, Sylvain (Advances in Social Sciences Research Journal, 2024)
Reconsideration of research methodologies becomes a necessity as academic disciplines and their publications have been proliferating relentlessly in recent decades. While research methodologies determine the pay-off as well as validity of academic research across scientific disciplines, research practice tends not to verge on assessing research methodologies. One reason might be that the concept research methodologies and the like usually come in the form of how-to-do section or book, leaving discussions to other sections/books of research. Another reason lies in the fact that research methodologies are seen as mere verbiage or theory. Yet, research methodologies furnish the tools with which to practice research. The present paper tracked major trails, concepts, and recurrent misunderstandings of both positivism and interpretivism. The paper did so to allow for sharper methodological toolkits and keener research.